Evaluation of nutritional status of paddy - Sumalee Anupotmontree; Nielsen, Jens Moller; Paiboon Prabuzdham; Holmberg, Soren; Government of the United Kingdom (Bangkok : Asian Institute of Technology, 1977)
The use of plant analysis as an aid in diagnosing nutritional disorders in rice has been proved a reliable method. A field experiment with paddy in the Central Plain of Thailand was designed to study the distribution of N, P, K, Na, Ca, Mg, Fe, Mn, Zn and Cu in rice plant parts periodically when grown under various combination rates of N and P application. The aim was to develop methods of quantitative diagnosis of the nutritional status of the young plant and prognosis of final yield, based on concentrations of nutrients at a fixed dry matter weight level of aerial parts of the plant and reference values for absolute and relative optimal concentration of the various nutrients. The development of the method followed the same principles as used in a recently developed fertilization system in Europe. ~he relationships be tween: (1) concentrations of various nutrients and dry matter weight of the plant, (2) grain yield at maturity and concentrations of various nutrients of the young plant, (3) concentrations of various nutrients and N concentration, and (4) concentrations of various nutrients and P concentration were taken into consideration. The similarity of the curves in these relationships with those found in various crops in Europe, indicated the possibility of transferring the European fertilization system to paddy cultivation in Southeast Asia.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Sc. ) - Asian Institute of Technology, 1977
Keywords: Rice research; Plants -- Nutrition